Kajian Penggunaan Green Infrastruktur dalam Upaya Penurunan Suhu Permukaan di Wilayah SWK Tegalega - Satrio Nugraha; Hilwati Hindersah; Irland Fardani (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Urban heat island is a phenomenon of temperature changes caused by the concentration of building density which causes the temperature in the area to be higher than in areas with a lower density concentration. SWK Tegalega is the 1st most populous area among SWK in Bandung City according to the 2011-2031 RTRW data for Bandung City with a total population density in 2020 reaching 415 people / Ha, SWK Tegalega has at least 2.87 ha of RTH from a total area of 67.75 ha with The number of buildings is 7,683 units according to DPMPTSP (Department of Investment and One Stop Integrated Service) of Bandung City, and based on Bandung City Regulation No. 10 of 2015 the designation of the SWK Tegalega area is used as the Mediapolis area (creative industry). The data used in this research include Landsat 8 OLI satellite imagery, population density data and google earth image maps. From the processing of Landsat 8 OLI, it produces several data such as LST, SAVI and NDBI, which are used by each of these data to determine the priority areas for handling high temperature locations. After that, 4 locations were determined for handling the temperature of the area, with the use of trade & service land, corridors, less dense settlements and dense settlements. Based on the 3D location, the average high temperature of the 4 locations ranges from 30.25 - 32.20OC. After applying the green infrastructure concept from the 4 locations, the average temperature reduction of each concept used is obtained, including the tree canopy concept which has an average temperature reduction of 2.60OC, the bioswale concept of reducing the temperature from this concept is 1.30OC, then the green roof concept has an average temperature reduction of 0.65OC and the green wall concept has an average temperature drop of <0.30OC. Based on the results of the analysis that has been carried out, the tree canopy concept is the most effective concept in reducing the temperature at the study location Abstrak. Urban heat island adalah fenomena perubahan suhu yang diakibatkan oleh konsentrasi kepadatan bangunan yang menyebabkan suhu diwilayah tersebut lebih tinggi dibandingkan dengan wilayah yang memiliki konsentrasi kepadatan lebih rendah. SWK Tegalega merupakan wilayah terpadat ke-1 antara SWK di Kota Bandung menurut data RTRW Kota Bandung 2011-2031 dengan total kepadatan penduduk tahun 2020 mencapai 415 jiwa/Ha, SWK Tegalega memiliki setidaknya 2,87 ha RTH dari luas total 67,75 ha dengan jumlah bangunan 7.683 unit menurut DPMPTSP (Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu) Kota Bandung, dan berdasarkan perda Kota Bandung no.10 tahun 2015 peruntukan kawasannya SWK Tegalega dijadikan sebagai wilayah Mediapolis (industri kreatif). Data yang digunakan dalam peneltian ini antara lain citra satelit Landsat 8 OLI, data kepadatan penduduk dan peta citra google earth. Dari pengolahan Landsat 8 OLI menghasilkan beberapa data seperti LST, SAVI dan NDBI, yang digunakan masing – masing data tersebut untuk mengetahui wilayah prioritas penanganan lokasi bersuhu tinggi. Setelah itu ditentukan 4 lokasi untuk penanganan suhu wilayah, dengan penggunaan lahan perdagangan & jasa, koridor, permukiman tidak padat dan permukiman padat. Berdasarkan 3D lokasi didapatkan suhu tinggi rata – rata ke-4 lokasi berkisar dari 30.25 – 32.20OC. Setelah diterapkan konsep green infrastruktur dari ke-4 lokasi tsb, maka didapatkan rata – rata penurunan suhu dari masing – masing konsep yang digunakan, antara lain konsep tree canopy memiliki rata – rata penurunan suhu sebesar 2.60OC, konsep bioswale penurunan suhu dari konsep ini sebesar 1.30OC, Kemudian konsep green roof memiliki rata – rata penurunan suhu 0.65OC dan Untuk konsep green wall memiliki rata – rata penurunan suhu < 0.30OC. Berdasarkan hasil analisis yang telah dilakukan konsep tree canopy menjadi konsep yang paling efektif dalam menurunkan suhu di lokasi studi.